Dinamika Agroforestry Tegalan di Perbukitan Menoreh, Kulon Progo, Daerah Istimewa Yogyakarta - Aditya Hani; Priyono Suryanto (Foresty Faculty of Hasanuddin University, 2014)
Land management in agroforestry systems requires species selection and proper silviculture. Selection of species and silvicultural treatments aimed at maintaining competition in obtaining a light, water and nutrients. Farmers choose the species based on the economical factor. This study aims to determine the composition of plant species in dry land agroforestry in Menoreh Hill, Kulon Progo District. Research done by survey method. Plot observation was divided into three level of light intensity: : a) early agroforestry (light intensity >50%), b) middle agroforestry, (light intensity 30-50%), c) further agroforestry (light intensity <30%). Four planting plots were made as repetition, so that there were 12 plots observation. Observations and measurements of vegetation are done with census (100%). The Result show five important value index in early Agroforestry,: sengon (77.84), coconut (50.04), and cacao (25.47), tree density was 482 trees/hectare and basal area 5.48 m2/ha, in middle agroforestry were: sengon (88.15), mahogany (49.51), and clove (45.03), with tree density was 595 trees/ha, and basal area was 6.70 m2/ha, further agroforestry were: clove (72.37%), sengon (50.61), and coconut (37.02), tree density was 650 trees/ha, basal area was 6.78 m2/ha.